METHODOLOGY TO DEVELOPMENT OF STUDENTS` WRITING SKILL THROUGH TECHNICAL TEXTS (American Journal of Research in Humanities and Social Sciences, 2023)
Writing requires the writer to demonstrate simultaneous control over multiple variables, making it an extremely challenging cognitive activity. Strong writing abilities may increase students' chances of success. Language cannot exist without writing. For all students to meet their educational and employment requirements, they must have strong writing abilities. The process approach places an emphasis on writing exercises that take students from idea generation and data collection all the way to the publication of a completed text. The process approach is learner-centered and takes into account the needs, expectations, goals, learning styles, skills, and knowledge of the students.